2020
DOI: 10.1037/dev0001073
|View full text |Cite
|
Sign up to set email alerts
|

Developmental changes in infants’ and children’s attention to faces and salient regions vary across and within video stimuli.

Abstract: Visual attention in complex, dynamic scenes is attracted to locations that contain sociallyrelevant features, such as faces, and to areas that are visually salient. Previous work suggests that there is a global shift over development such that observers increasingly attend to faces with age. However, no prior work has tested whether this shift is truly global, that is, consistent across and within stimuli despite variations in content. To test the global shift hypothesis, we recorded eye movements of 89 childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 75 publications
0
21
0
Order By: Relevance
“…We chose to use these saliency models for several reasons. First, they are commonly used in understanding infants’ fixation (Kadooka & Franchak, 2020; Kelly et al, 2019; Mahdi et al, 2018; Simpson et al, 2019). Thus, a systematic investigation of how well these models predict infants’ fixations will be useful for the interpretation of these other findings.…”
Section: Methodsmentioning
confidence: 99%
“…We chose to use these saliency models for several reasons. First, they are commonly used in understanding infants’ fixation (Kadooka & Franchak, 2020; Kelly et al, 2019; Mahdi et al, 2018; Simpson et al, 2019). Thus, a systematic investigation of how well these models predict infants’ fixations will be useful for the interpretation of these other findings.…”
Section: Methodsmentioning
confidence: 99%
“…First, rates of looking at salient areas and faces are highly dependent on the particular video stimuli. When comparing across a wide range of ages (6 months to 12 years) and across a large, diverse set of video stimuli, there was no evidence for consistent age differences in either looking at salient areas or at faces across video clips (Kadooka & Franchak, 2020). Although a few clips showed age trends, age differences were not evident for most stimuli.…”
Section: Introductionmentioning
confidence: 98%
“…And although centering is a strong cue for adults’ orienting to faces in videos (Xu et al., 2018), no study has tested whether centering relates to face looking in infants and children. Previous research found considerable variability in rates of looking at faces, rates of looking at salient areas, and the saliency of faces across video stimuli (Frank et al., 2012; Kadooka & Franchak, 2020; Stoesz & Jakobson, 2014; Wass & Smith, 2015). Accordingly, it was important for the current investigation to test saliency and centering cues for face looking across a large stimulus set with multiple faces that vary in appearance and location over time.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations